Pharmacological activities of bioactive compounds isolated from Acacia pennata (L) Willd.: A comprehensive update and application of in-silico techniques for repurposing (Sciences of Phytochemistry, 2022)
Bioactive compounds (BACs) are naturally occurring compounds with pharmacological activities. BACs isolated from plants have significantly contributed to modern medicine. Multiple studies had reported the isolation of BACs with diverse pharmacological activities from Acacia pennata (L.) Willd. This review aims to compile all the available data on the pharmacological activities of the BACs that had been isolated from A. pennata. An online literature survey was carried out on academic databases namely Scopus, Science Direct, PubMed, and Google Scholar. Keywords such as ‘Acacia pennata’, ‘isolated compound’, and ‘pharmacological activity’ were used, either alone or in combination. A total of 52 articles published between the year 1980 to 2020 that contained relevant information on A. pennata were identified and collected. To date, a total of 29 compounds had been isolated from A. pennata. The compounds isolated from A. pennata belonged to secondary metabolites namely triterpenoid ketone, ceramide, alkaloid, saponin, flavonoid-glycoside, and terpenoid. A total of 22 BACs had been evaluated for biological activities such as anti-Alzheimer, anti-inflammatory, antioxidant, anti-diabetic, anti-obesity, anti-viral, anti-nociceptive, and anti-cancer activities. The pharmacological activities of 7 compounds isolated from A. pennata remained unexplored. A total of 14 compounds that had been isolated from A. pennata were also reported to be isolated from other plants. This comprehensive review provides an update on all the pharmacological works that had been carried out on the isolated BACs of A. pennata to date. In-silico techniques may be applied to repurpose the isolated BACs of A. pennata prior to wet lab studies.